2011
DOI: 10.1177/0961203310393769
|View full text |Cite
|
Sign up to set email alerts
|

Lambert–Eaton Myasthenic syndrome and follicular thymic hyperplasia in systemic lupus erythematosus

Abstract: Fatigue is a prominent feature of systemic lupus erythematosus (SLE), usually ascribed to various factors, such as muscle or joint involvement, anaemia or depression. The Lambert-Eaton myasthenic syndrome (LEMS) is a rare autoantibody-mediated disorder of neuro-muscular transmission. We report on a well-defined LEMS associated with thymus hyperplasia in a SLE patient. An African 41 years-old SLE patient presented with persisting fatigue, myalgia and dyspnea, abolished reflexes and a bilateral ptosis. Neuromusc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…The Morimoto et.al. and the Pasqualoni et al patients had LEMS with thymic hyperplasia . The Roohi et al patient represented MG with a positive VGCC‐ab in view of the MG pattern on the RNS test .…”
Section: Resultsmentioning
confidence: 98%
“…The Morimoto et.al. and the Pasqualoni et al patients had LEMS with thymic hyperplasia . The Roohi et al patient represented MG with a positive VGCC‐ab in view of the MG pattern on the RNS test .…”
Section: Resultsmentioning
confidence: 98%
“…The presence of thymoma is found in 30% of patients with clinically manifested SLE while in 30% of cases it was discovered by accident, radiographically, as it was a case with our patient. The clinical picture of SLE is clearly visible, including all immunoserological activity indicators 5,6,[10][11][12][13] . For the final diagnosis, given the example of our patient, we found that an additional diagnostics was necessary, such as bronchoscopy with TBB and needle biopsy of changes in the mediastinum.…”
Section: Discussionmentioning
confidence: 99%
“…This was the case with our patient, too. However, the connection between the disorder of thymic function and SLE deserves attention and additional studies, especially when the therapeutic effects of thymectomy are considered 5,8,10,13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thymus hyperplasia and thymoma are well‐known entities of MG. Reports of thymic hyperplasia associated with other autoimmune diseases also exist . Thymus plays an important role in T‐cell function on recognizing self‐ vs non‐self‐antigens.…”
Section: Discussionmentioning
confidence: 99%